2020
DOI: 10.1111/1365-2435.13679
|View full text |Cite
|
Sign up to set email alerts
|

Trait filtering during exotic plant invasion of tropical rainforest remnants along a disturbance gradient

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 82 publications
(123 reference statements)
2
31
0
Order By: Relevance
“…For example, two of the most widespread invaders in the tropics, Miconia crenata (formerly Clidemia hirta) and Lantana camara (Figure 3a-b), are dispersed by frugivores (DeWalt & Hamrick 2004;Ramaswami et al 2016). In line with this fact, Waddell et al (2020b) showed that successful invasion of tropical forests requires adaptations for longdistance dispersal (e.g., by vertebrates) as well as traits related to competitive ability, such as being tall and woody. Thus, for disturbed tropical forests at least, evidence points towards the role of plant-dispersal mutualisms as agents for widespread distributions of non-native plants in forests.…”
Section: ) or Reflective Of Past Human Choices In What Types Of Species They Introduced Into Tropical Versus Temperate Ecosystems (Vanmentioning
confidence: 82%
“…For example, two of the most widespread invaders in the tropics, Miconia crenata (formerly Clidemia hirta) and Lantana camara (Figure 3a-b), are dispersed by frugivores (DeWalt & Hamrick 2004;Ramaswami et al 2016). In line with this fact, Waddell et al (2020b) showed that successful invasion of tropical forests requires adaptations for longdistance dispersal (e.g., by vertebrates) as well as traits related to competitive ability, such as being tall and woody. Thus, for disturbed tropical forests at least, evidence points towards the role of plant-dispersal mutualisms as agents for widespread distributions of non-native plants in forests.…”
Section: ) or Reflective Of Past Human Choices In What Types Of Species They Introduced Into Tropical Versus Temperate Ecosystems (Vanmentioning
confidence: 82%
“…S3 in supplementary material). This result seems to suggest that more resource-limited environments filter out traits substantially diverging from the locally-adapted native community from this family (Waddell et al 2020).…”
Section: Resultsmentioning
confidence: 79%
“…However, it is worth highlighting that alternative explanations may also explain the observed patterns, or may be acting in tandem with the effects of human foraging (Adnan et al, 2015; Brockerhoff et al, 2017). First, edible and inedible species may have different trait values, especially if traits are linked with edibility (e.g., traits related to tissue density; Lueder et al, 2022; Waddell et al, 2020). If edibility‐related traits also affect dispersal ability or the ability of species to cope with the abiotic environment (as in tissue density traits), then the edible‐inedible comparison may not reflect the effect of humans but that of trait–environment interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Second, while we classified species as edible based on interviews with local villagers, we cannot discount the role of other animal taxa in dispersing the edible species (Teitelbaum & Mueller, 2019). As data on species traits and interaction networks in the study area are not available, we recommend conducting further study involving abiotic factors and functional traits to validate these findings (Lueder et al, 2022; Waddell et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation